Pre-deployment training of UN women military peacekeepers: a case study analysis of three south-east Asian countries - Fitriani (Cranfield University, 2017)
The purpose of this study is to examine the role and impact that uniformed women play in UN peacekeeping operations, and to further establish how appropriate pre-deployment training (PDT) supports the performance of women in operational zones. The research questions posed are ‘whether women make a difference to peacekeeping operations’ and ‘to what extent PDT enables them to do so’. To answer these questions, the thesis takes a two-pronged approach. Firstly, a literature search evaluates the nature of uniformed women’s participation in UN peacekeeping missions, their contribution to effective peacekeeping and the UN policies supporting women’s participation in its missions. The main resources accessed for the literature research are the UN and contributing countries’ official policies, publication and reports. Secondly, primary data were acquired through field research on the training needs of three Southeast Asian countries, namely Indonesia, the Philippines and Country A. Across these sample states, empirical research data was gathered through in-depth semi-structured interviews with 37 female peacekeepers, 17 trainers and seven decision-makers. The literature reveals that women participate in UN peacekeeping missions in two ways, those that form part of a contingent and others that act as individual military experts, observers or staff officers. Women make a difference by allowing a UN mission to have greater reach to the local community, especially to the female population in segregated communities, including the survivors of sexual- and gender-based violence. The field research also reveals that the three Southeast Asian country case studies provide different PDT to their personnel, although the UN provides standardised training materials. Interview data from all three countries indicate that women and men receive combined PDT training, with the majority of the respondents arguing that there is no need for segregated gender training. However, they endorse differentiated training for specialist skills, such as for mentoring teams by same sex members to discuss biological and logistical issues in deployment, including, for instance, the best strategy for ensuring continuity in the supply of women’s sanitary requirements. Not all the three sample countries support uniformed women deployment on par with male peacekeeper deployment, and rarely support women holding leadership positions, due to discrimination in military education access, limitations on human resources and apprehension at putting women into dangerous positions. Such constraints limit the roles that women can play in UN field missions.